Speech Acts Analysis on Teaching and Learning Process Used by the Teacher in MAN 2 Mataram in Academic Year 2016-2017 - Yulia Isnaini (Muhammadiyah University of Mataram, 2017)
This study was aimed at finding out Speech Acts Analysis on Teaching andLearning Process used by the Teacher in MAN 2 Mataram in Academic year 2016/2017. The method of this research is qualitative research The data of this research were the utterances performed by the Teachers of MAN 2 Mataram. The research instrument was the researcher himself. Participant is the subject from which the data obtained (Arikunto, 2010: 172)The Researcher’s participant actively classification speech act by the Teachers on teaching and learning process.T he instrument of data by using video camera and observation. To analyze the data Based on Louis (2005:181). This study used observation and video recording as an instrument of data collection, the researcher applied coding system. In this research, there are two validity principles applied by the researcher. The results of the research show that there are three classifications of speech act performed by the Teachers in the aching and learning process . The results of the research show that there are three classification of speech act performed by the Teachers in the aching and learning process. they are 4 data of locutionary act , 30 data of Illucotionary act, 7 data of Perlocutionary act . So the total of data were 41 data of speech act are used By the Teachers in MAN 2 Mataram.